Development and Performance of Cement Bound Materials in Road Pavements - Hassan, Khaled E.; El-Hussain, Osman; Al-Kuwari, Mohammed bin-Saif; Al-Emadi, Khalid (Proceedings of the International Conference on Civil Infrastructure and Construction (CIC), 2020)
The use of cement bound materials (CBMs) for road construction in Qatar is relatively new. CBM improves the structural capacity and durability of pavement, but considerations should be made to the setting time and strength development in hot arid environment, such as in Qatar. The paper presents a laboratory development and performance characteristics of CBM mixtures, with environmental and economic benefits through the use of local and recycled materials. The developed mixtures showed full compliance with the grading, strength and durability requirements of the Qatar Construction Specifications (QCS, 2014). Site data from Ashghal projects indicated the difficulty of producing consistent strength in practice, with the potential of increased strength and associated risk of reflection cracking in the asphalt overlaying. Recommendations are made to improve the construction practice and specification of cement and other hydraulically bound materials to enhance the service life of pavement and support the government strategy of sustainable construction.